2007
DOI: 10.1021/jo7020345
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonative Metalation of Five-Membered Aromatic Heterocycles Using Mixed Lithium−Zinc Species

Abstract: Deprotonation of benzoxazole, benzothiazole, benzo[b]thiophene, benzo[b]furan, N-Boc-protected indole and pyrrole, and N-phenylpyrazole using an in situ mixture of ZnCl(2).TMEDA (0.5 equiv) and lithium 2,2,6,6-tetramethylpiperidide (1.5 equiv) in THF at room temperature is described. The reaction was evidenced by trapping with iodine, regioselectively giving the expected functionalized derivatives in 52-73% yields. A mixture of mono- and disubstituted derivatives was obtained starting from thiazole. Cross-coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(51 citation statements)
references
References 57 publications
1
48
0
Order By: Relevance
“…Molecular structure of [(TMEDA)Na(TMP)(CH 2 PCH 3 Ph)Mg(TMP)] 2 with thermalellipsoids at 40 %p robability.H ydrogen atomsh ave been omitted for clarity.Selected bond lengths( )a nd angles (8): Mg(1)ÀN(1), 2.069(5); Mg(1)ÀN(2), 2.001(5); Mg(1)ÀC(1), 2.182(6);Na(1)ÀN(1), 2.463(5); Na(1)ÀN(3), 2.528(6); Na(1)ÀN(4), 2.495(5);Na(1)ÀP(1), 2.919(2);P (1)ÀC(1), 1.777(6); P(1)ÀC(2), 1.823 (8);N(1)-Na(1)-P(1), 95.24 (12); Na(1)-N(1)-Mg(1), 103.5(2);N (1)-Mg(1)-C(1), 108.8(2); Mg(1)-C(1)-P(1), 118.4(3); C(1)-P(1)-Na(1), 88.40 (19). (16); Mg(1)ÀN(2), 1.9989 (17);N a(1)ÀC(3), 3.036(2);Na(1)ÀC(4), 2.648(2);N a(1)ÀN(3), 2.4779(18);Na(1)ÀN(4), 2.5401(18); Na(1)ÀN(5),2 .5291 (18);N(2)-Mg(1)-C(3), 120.48 (8); N(2)-Mg(1)-N(3), 134.32 (7); N(3)-Mg(1)-C(3), 105.16 (7); Na(1)-N(3)-Mg(1), 89.35 (6). (3); Na(1)ÀN(2), 2.457(3); Na(1)ÀN(4), 2.569(3); Na(1)ÀC(2), 3.038(4);Na(1)ÀC(3), 2.684(4); N(1)-Mg(1)-N(3), 133.51 (13);N(1)-Mg(1)-C(3), 119.21 (14);C(3)-Mg(1)-N(3), 107.11 (13);N a(1)-N(3)Mg(1), 87.25 (11).…”
Section: Solid-state Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular structure of [(TMEDA)Na(TMP)(CH 2 PCH 3 Ph)Mg(TMP)] 2 with thermalellipsoids at 40 %p robability.H ydrogen atomsh ave been omitted for clarity.Selected bond lengths( )a nd angles (8): Mg(1)ÀN(1), 2.069(5); Mg(1)ÀN(2), 2.001(5); Mg(1)ÀC(1), 2.182(6);Na(1)ÀN(1), 2.463(5); Na(1)ÀN(3), 2.528(6); Na(1)ÀN(4), 2.495(5);Na(1)ÀP(1), 2.919(2);P (1)ÀC(1), 1.777(6); P(1)ÀC(2), 1.823 (8);N(1)-Na(1)-P(1), 95.24 (12); Na(1)-N(1)-Mg(1), 103.5(2);N (1)-Mg(1)-C(1), 108.8(2); Mg(1)-C(1)-P(1), 118.4(3); C(1)-P(1)-Na(1), 88.40 (19). (16); Mg(1)ÀN(2), 1.9989 (17);N a(1)ÀC(3), 3.036(2);Na(1)ÀC(4), 2.648(2);N a(1)ÀN(3), 2.4779(18);Na(1)ÀN(4), 2.5401(18); Na(1)ÀN(5),2 .5291 (18);N(2)-Mg(1)-C(3), 120.48 (8); N(2)-Mg(1)-N(3), 134.32 (7); N(3)-Mg(1)-C(3), 105.16 (7); Na(1)-N(3)-Mg(1), 89.35 (6). (3); Na(1)ÀN(2), 2.457(3); Na(1)ÀN(4), 2.569(3); Na(1)ÀC(2), 3.038(4);Na(1)ÀC(3), 2.684(4); N(1)-Mg(1)-N(3), 133.51 (13);N(1)-Mg(1)-C(3), 119.21 (14);C(3)-Mg(1)-N(3), 107.11 (13);N a(1)-N(3)Mg(1), 87.25 (11).…”
Section: Solid-state Structuresmentioning
confidence: 99%
“…[14,15] These metallating agents usually consist of a mixeda lkyl or amido lithiums peciesw ith either ad ivalent metals alt or ad ialkyl/amido metallic species. Of particular relevance to this work are the bimetallicb ases formed by the cocomplexation of an alkali metal amide (most commonly NaTMP) and ad ialkyl subordinate metal partner, typically zinc, [12,[16][17][18] magnesium [14,15,19,20] aluminium [21,22] or manganese. [23][24][25] Early examples of the effectiveness of these bases include the magnesiation (CÀHt oC ÀMg) of benzene [26] and the selective meta-magnesiation of toluene, [27] both achieved utilising the sodium magnesiate base [(TMEDA)Na(nBu)-(TMP)Mg(TMP)].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that it is a 1:1 LiTMP-Zn(TMP) 2 combination. While LiTMP deprotonates the substrate, Zn(TMP) 2 intercepts the generated aryllithium [18,19,22]. A recent computer study on anisole showed that the reactive species is solvated LiTMP.…”
Section: Resultsmentioning
confidence: 99%
“…The use of in situ metal traps avoids the use of cryogenic conditions to achieve these reactions [16,17]. We have developed mixed lithium-zinc combinations based on TMP (TMP = 2,2,6,6-tetramethylpiperidino) capable of deprotonating sensitive substrates at temperatures close to rt [18,19,20,21]. In order to obtain original scaffolds such as pyrazino-fused carbazoles and carbolines, we decided to combine this deprotometalation under in situ trapping conditions with palladium- and copper-catalyzed coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrimidine 2 being prone to nucleophilic attacks, 6 we first tried to use the base prepared in situ by mixing ZnCl 2 ·TMEDA and LiTMP in a 1:3 ratio, 7 and supposed to be a 1:1 LiTMP·2LiCl(±TMEDA)-Zn(TMP) 2 mixture. 8 It proved not appropriate, with the iodide 4a isolated in a low 18% yield when the deprotonation step was performed at 0 °C and only degradation noticed at higher temperatures.…”
Section: Scheme 2 Synthesis Of the Diaryl Ketones 1a-imentioning
confidence: 99%